INTERPRETATION OF ABD GAFUR'S SPEECH DEIXIS IN "SCHOOL OF LAW GRADUATE CONVOCATION SPEAKER BOSTON UNIVERSITY 2018" (Karya Ilmiah Mahasiswa (KIMA), 2022)
The objective of this research is to investigate the types of deixis that are predominantly used in Abd Gafur's speech in “School of Law Graduate Convocation Speaker Boston University 2018. The data was obtained from Abd Gafur's speech on the YouTube channel. The research was conducted in the form of notes taking e-papers. The findings showed that there were 55 data of deixis. After analyzing the data, the writer found that there were four types of deixis found in Abd Gafur's speech such as; person deixis, spatial deixis, temporal deixis, and social deixis. After analyzing the data, the most frequent deixis found in Abd Gafur's speech sequentially were person deixis (58.18%), spatial deixis (16.36), social deixis 26.67%, and temporal deixis (10.91).